Chamomile gel versus urea cream to prevent acute radiation dermatitis in head and neck cancer patients : results from a preliminary clinical trial - Ferreira, Elaine Barros (2020)
We assessed safety and potential efficacy of a chamomile gel compared with urea cream to prevent acute radiation dermatitis in head and neck cancer patients. We assessed safety and potential efficacy of the chamomile gel in escalating concentrations of 2.50%, 5.00% and 8.35% of chamomile. Concentration of 8.35% was chosen for a randomized trial comparing chamomile gel (8.35%) with urea cream (n=24per group), for potential efficacy to delay or prevent radiation dermatitis in these patients. Preliminary results demonstrate a delayed onset of dermatitis, with onset of Grade 2 dermatitis at 5.1 (1.3) weeks in the chamomile group and 4.5 (1.3) weeks in the urea group (effect size of 0.46). Itching, burning and hyperpigmentation were more frequently reported in the urea group. Results indicates a potential efficacy of the chamomile gel. Further studies are needed to confirm the effect of the chamomile gel in reducing or delaying the occurrence of radiation dermatitis.